The relationship between personality traits of supervisor and supervisees' development among medical trainees mediated by working alliance - Masyitah binti Minhad (Kulliyyah of Islamic Revealed Kowledge and Human Sciences, International Islamic University Malaysia, 2017)
Medical supervisors who are assigned to train medical trainees usually focus on the standard operating procedures, the manual logbooks and the syllabus required to be fulfilled. The psychological factors of the medical trainees are usually neglected and underestimated. This research sought to explore the relationship between personality traits of the supervisor and the supervisees' development among medical trainees with working alliance as the mediator. The study uses conceptual framework that combine theoretical framework of Values Effects by Meglino and Ravlin (1998) and Integrated Developmental Model by Stoltenberg and Delworth (1987) which has been revised by Bernard and Goodyear (1998). There are four instruments used in this study, namely; TAJMA Personality Profiles Second Edition which is used to measure medical supervisors' personality traits, Supervisee Questionnaires Level-Revised to measure medical trainee development, Supervisory Working Alliance for Supervisor and Supervisory Working Alliance for Trainees to measure supervisory working alliance. 128 respondents with equal distribution of medical supervisor and medical trainees participated in this study. There are four hospitals involved in this research: Hospital Kajang, Hospital Serdang, Hospital Ampang and Hospital Raja Permaisuri Bainun, Ipoh. The findings indicate that working alliance is the mediator for personality traits of the supervisors and medical trainees' development. It is also revealed leadership, patriotism, achievement, and cross cultural traits are significant to enhance supervisory working alliance and to ensure medical trainees' development. These findings are discussed with respect to the literature on personality traits of the supervisors, medical trainees' development, and supervisory working alliance. This study may help future medical supervisors to adopt traits that may help medical graduates to develop professionally.